Women's entrepreneurship and internationalization: patterns and trends. Issue 9 (6th August 2018) - Ratten, Vanessa; Tajeddini, Kayhan
Abstract : Purpose: The purpose of this paper is to review the literature on women's entrepreneurship and internationalization in order to build an understanding about future trends. There is increasing interest in the role of women in entrepreneurship yet little research has been conducted about the link to internationalization patterns. Design/methodology/approach: The literature is reviewed based on a systematic analysis of the words women, female, gender and internationalization. Findings: Three main schools of thought around women's entrepreneurship and internationalization (philosophy, management and motivations) are then discussed. The analysis of literature and classification into main theories enables the building of new research around women's entrepreneurship and internationalization. Originality/value: There is a pipeline of women intending to become entrepreneurs so this paper helps to understand how women entrepreneurs influence internationalization patterns and how to help support women in their business endeavors.